Level of reactivity of IgM anticardiolipin antibodies in preeclampsia: a likely early serologic marker - Karla N. Pereira; Sandra T. Beck; Cristine K. Konopka; Zanoni Segala; Rafael N. Moresco; José E. P. Silva (Sociedade Brasileira de Patologia Clínica, 2015)
The purpose of this study was to measure the level of anticardiolipin antibodies in preeclamptic pregnant women to verify a possible association between the presence of these antibodies and the development of the syndrome. A total of 36 pregnant women with preeclampsia and 19 women with normal pregnancy were evaluated. Anticardiolipin antibodies were determined by enzyme immunoassay. The reactivity level of anticardiolipin antibodies was significantly higher in the preeclamptic group, with a significance level of 95%. The results can mean the participation of anticardiolipin antibodies in the pathogenesis of preeclampsia. Future studies may confirm this parameter as an early marker for the development of this disease.